The Moderating Effect of Information Flow on the Relationship between Management Risk and Performance of Manufacturing Firms in Kenya - Kithuka, James; Guyo, Wario; Kiarie, David (International Journal of Supply Chain Management, 2022)
Purpose: The study also sought to address the moderating effect of information flow on the relationship between management risk and performance of manufacturing firms. Information flow plays an integral role in determining the effectiveness of supply chain processes and how they enhance firm performance. Outsourcing logistics comes with varied risks and one of the risks is management risks. These risks are aligned with the administrative differences between the outsourced company and the manufacturing firm, which could affect the effectiveness of the cooperation towards enhanced performance. Methodology: The study was informed by core competency theory. Both descriptive and explanatory research designs were adopted. The unit of observation was the supply chain administrators of manufacturing firms in Kenya. Stratified sampling was conducted on all the one thousand one hundred and twenty three manufacturing firms registered by KAM, simple random sampling was carried out on the strata to identify a sample size of 295 firms. The study relied on primary data which was collected through semi-structured questionnaires that were administered to administrators charged with the management of supply chain within the selected firms. Data analysis was done using descriptive statistics namely percentages, mean and standard deviation through the help of SPSS. Findings: The study revealed that management risk significantly influenced the performance of manufacturing firms in Kenya. The findings further revealed that information flow had a positive but insignificant moderating effect on the relationship between management risk and performance of manufacturing firms in Kenya. Unique Contribution to Theory, Practice and Policy: The study concluded management risk is essential in the performance of manufacturing firms in Kenya.